2017
DOI: 10.3390/ijerph14020213
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Carbonic Anhydrase 9 in the Alimentary Canal of Aedes aegypti and Its Relationship to Homologous Mosquito Carbonic Anhydrases

Abstract: In the mosquito midgut, luminal pH regulation and cellular ion transport processes are important for the digestion of food and maintenance of cellular homeostasis. pH regulation in the mosquito gut is affected by the vectorial movement of the principal ions including bicarbonate/carbonate and protons. As in all metazoans, mosquitoes employ the product of aerobic metabolism carbon dioxide in its bicarbonate/carbonate form as one of the major buffers of cellular and extracellular pH. The conversion of metabolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Specifically, CA has been proposed to play an important role in bicarbonate metabolism, pH regulation and ions transportation in the alimentary canal of Ae. aegypti [ 38 ]. Thus, its inhibition is a strategy to explore for the development of larvicidal compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, CA has been proposed to play an important role in bicarbonate metabolism, pH regulation and ions transportation in the alimentary canal of Ae. aegypti [ 38 ]. Thus, its inhibition is a strategy to explore for the development of larvicidal compounds.…”
Section: Resultsmentioning
confidence: 99%
“…albimanus , when exposed to gradual changes in saline water, specialized non-dorsal anterior rectal (non-DAR) cells undergo changes in the localization of V-type ATPases and K+/Na+ ATPases proteins, allowing the production of super osmotic urine and disrupting the ion reabsorption system in non-DAR cells (8, 9). Other studies in mosquitoes have also suggested the importance of Carbonic Anhydrase (CA) and aquaporins to osmoregulation in saline environments (10, 12). We found that An.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the tolerance of An. albimanus to saltwater also suggest the importance of V-type ATPase, carbonic anhydrase, and K+/Na+ ATPase proteins to osmoregulation (8)(9)(10)(11)(12), and studies in other insects have shown the role of aquaporins in such process. Orthology searches suggest that An.…”
Section: Osmoregulation Ion Metabolism and Transportmentioning
confidence: 99%
See 1 more Smart Citation